Ragam Kalimat Interogatif pada Antologi Cerpen "Alona Ingin Menjadi Serangga" Karya Mashdar Zainal Berdasarkan Frasa Pengisi Setiap Fungsi Sintaksis - Mukram, Poppy Trywahyuni (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
ABSTRACTThis research aims to describe the pattern of functions (S-P-O-K-Pel) in interrogative sentences,and phrases filling the functions of subject, predicate, object, description, and complement inthe short story anthology "Alona Ingin Menjadi Serangga". In addition, it can draw conclusionson the similarities and differences between current and previous research. The focus of thisresearch are: 1) looking for data sources that match the title, namely "Alona Ingin MenjadiSerangga"; 2) grouping data quotations based on syntactic function-filling phrases; 3)analyzing data quotations based on syntactic function-filling phrases; 4) making conclusions.The method used in this research is to use a qualitative approach with document studytechniques. The object of study and analysis in this research is the anthology of short storiesAlona Ingin Menjadi Serangga by Mashdar Zainal. The results obtained are various types ofsyntactic function patterns and phrases filling each subject function in the form of noun phrases,phrases filling each predicate function in the form of noun phrases, verbs, numeralia, andadjectives. Then the phrases filling each object function are noun and verb phrases; phrasesfilling each adverbial function are noun phrases, verbs, adverbs, adjectives, and prepositions.Also, phrases filling each complementary function are in the form of noun and adverb phrases.Keywords: Filler phrases of each function, Syntax, Short Story, Qualitative, Document Study.